2017
DOI: 10.1177/1524838017730648
|View full text |Cite
|
Sign up to set email alerts
|

Who Are the Victims and Who Are the Perpetrators in Dating Violence? Sharing the Role of Victim and Perpetrator

Abstract: Further efforts should be put into avoiding categorization of those involved in violence; rather, they should be regarded as a single group. Additionally, evidence-based interventions should be developed for this population to help break the cycle of violence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 47 publications
5
27
0
1
Order By: Relevance
“…A growing body of IPA literature, along with a meta-analysis of 25 peer-reviewed studies by Park and Kim (2019), have revealed that there is a significant overlap between IPA victimization and perpetration in most couples that experience violence. It suggests that some of the male and female victims have also perpetrated IPA.…”
mentioning
confidence: 99%
“…A growing body of IPA literature, along with a meta-analysis of 25 peer-reviewed studies by Park and Kim (2019), have revealed that there is a significant overlap between IPA victimization and perpetration in most couples that experience violence. It suggests that some of the male and female victims have also perpetrated IPA.…”
mentioning
confidence: 99%
“…For example, a meta-analysis by Park and Kim revealed that participants who experienced violence earlier were more likely to perpetrate or become the victims of DV (S. Park & Kim, 2019). While most of the determinants were reported as risk factors for DV, individual characteristics like self-control (Hébert et al, 2019) and conflict resolution skills (Spencer et al, 2019) have been reported as protective factors against DV.…”
Section: Determinants Of DVmentioning
confidence: 99%
“…Interestingly, fewer studies examined characteristics and profiles of perpetrators of dating violence. In their meta-analysis of the patterns of involvement in dating violence, Park and Kim (2017) found that those who identified themselves as dating violence perpetrators had a previous victimization experience. Unsurprisingly, teens who experienced dating violence perpetration were more likely to be involved with antisocial peers or to be part of aggressive peer groups (Ellis, Chung-Hall, & Dumas, 2012;Swahn, Simon, Arias, & Bossarte, 2008).…”
Section: Teen Involvement In Violent Dating Relationshipsmentioning
confidence: 99%